2021
DOI: 10.3390/jcm10112247
|View full text |Cite
|
Sign up to set email alerts
|

Predicting One-Year Deaths and Major Adverse Vascular Events with the Controlling Nutritional Status Score in Elderly Patients with Non–ST-Elevated Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: The prognostic value of malnutrition in elderly patients with non-ST-elevated myocardial infarction (NSTEMI) is not fully understood. Nutritional characteristics were evaluated by novel Controlling Nutritional status (CONUT), the prognostic nutritional index (PNI) and the geriatric nutritional risk index (GNRI) scores. The impact of these scores on major outcomes in 253 NSTEMI patients over 60 years and older were assessed. Compared to those with good nutritional status; malnourished patients had more major ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…After a more detailed review,48 references were excluded for different reasons. For the final analysis, nine ( 13 , 24 , 25 , 29 34 ) observational studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a more detailed review,48 references were excluded for different reasons. For the final analysis, nine ( 13 , 24 , 25 , 29 34 ) observational studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…The lower level of the laboratory variables used to calculate the CONUT score has shown to be associated with disease progression and mortality in patients with CAD ( 18 23 ). Furthermore, when compared to other nutrition-related measures in patients with CAD, recent studies have demonstrated that the CONUT score has the highest predictive ability for mortality and MACE ( 24 , 25 ). However, no previous meta-analysis has specifically addressed the predictive value of CONUT score for all-cause mortality and MACE in this population group.…”
Section: Introductionmentioning
confidence: 99%
“…Several nutritional scoring systems, including the prognostic nutritional index (PNI), CONUT, triglycerides-total cholesterol-body weight index (TCBI), Mini Nutritional Assessment (MSA), Graz Malnutrition Screening (GMS), and GNRI have been introduced for evaluating nutritional state in clinical practice. Malnutrition determined by the PNI ( 23 ), TCBI ( 24 , 25 ), and CONUT ( 3 ) was also significantly associated with adverse outcomes in patients with CAD ( 23 ). However, there is no consensus on which tools have the best predictive role in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies ( 7 11 ) have investigated the associations of GNRI with adverse outcomes in patients with CAD. However, the predictive value of GNRI was not fully established in this population due to the presence of conflicting results ( 3 , 12 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation